The Influence Of Financial Literacy, Financial Self-Efficacy, Financial Behavior Of Paylater Users In The Millennial Generation And Generation Z In Pontianak City - Anisa Dinda Rizky; Heni Safitri; Dedi Hariyanto (UNIVED Press, 2025)
His research aims to determine whether financial literacy, financial self-efficacy, and financial stress influence the financial behavior of PayLater users among millennials and Generation Z in Pontianak City. Using a positive data collection strategy and a sample size of 150 participants, this study adopts an associative methodology. Eligible participants are Pontianak City residents aged 17–44 years and PayLater users. Statistical methods employed in the analysis include multiple linear regression, correlation and determination coefficients, simultaneous testing (F test), and partial testing (t test). The analyzed data is linear, normally distributed, and shows no signs of multicollinearity, as confirmed by the classical assumption test. The research variables exhibit a strong relationship, as indicated by a correlation value of 0.753. According to the coefficient of determination (R²), the variables examined in this study explain 56.7% of the variance in financial behavior, while the remaining 43.3% is influenced by other factors not addressed in this study. Preliminary findings indicate that financial literacy and financial self-efficacy significantly influence financial behavior positively. In contrast, financial stress has a positive effect but is not statistically significant in influencing financial behavior.